2002
DOI: 10.1111/1467-6486.00326
|View full text |Cite
|
Sign up to set email alerts
|

Formal Mentoring Systems: An Examination of the Effects of Mentor/Protégé Cognitive Styles on the Mentoring Process

Abstract: In informal mentoring systems, protégés seek help from other organizational members between whom there is often mutual attraction and rapport resulting in a level of interpersonal comfort between the members of the relationship. Because of the apparent benefits for both employee and organization, many human resource managers now attempt to establish formal mentoring systems in which mentors and protégés are brought together systematically. It is recognized, however, that assigned mentoring relationship… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
89
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(96 citation statements)
references
References 0 publications
2
89
0
2
Order By: Relevance
“…Like the study conducted by Armstrong et al (2002), mentoring participants who demonstrated mutual liking not only enhanced the quality of mentoring relationships, but also, in our cohorts, gave strong indications that they would continue their relationship after the formal part of the program had concluded.…”
Section: The Personal Nature Of Mentoringsupporting
confidence: 56%
“…Like the study conducted by Armstrong et al (2002), mentoring participants who demonstrated mutual liking not only enhanced the quality of mentoring relationships, but also, in our cohorts, gave strong indications that they would continue their relationship after the formal part of the program had concluded.…”
Section: The Personal Nature Of Mentoringsupporting
confidence: 56%
“…Studies on cognitive style congruence have mostly used the difference score approach or median split (Allinson et al, 2001; Armstrong et al, 2002Armstrong et al, , 2004Armstrong & Priola, 2001;Lin et al, 2010;Vanderheyden & De Baets, 2015), the polynomial regression analysis approach used in the current study preserves the independent effect of each component measure (Shanock et al, 2010). Polynomial regression and surface analysis allowed us to analyze communication satisfaction in four major settings which would not be possible by using difference scores.…”
Section: Data Analysis and Findingsmentioning
confidence: 99%
“…A significant shortcoming of existing studies on cognitive style congruence is the fact that they have used a difference score approach to measure the absolute distance between cognitive style scores of the dyads or a median split approach to categorize the cognitive styles (Allinson, Armstrong, & Hayes, 2001;Armstrong, Allinson, & Hayes, 2002, 2004Armstrong & Priola, 2001;Lin, Kao, & Chang, 2010;Vanderheyden & De Baets, 2015). The difference score fails to differentiate between the relationship among an analytic manager managing an intuitive employee and an intuitive manager managing an analytic employee, since the difference in the scores would be the same in both cases.…”
Section: Introductionmentioning
confidence: 99%
“…Because the characteristics of two people in a relationship influence the extent and quality of their interactions between each other (Hinde, 1997;Neyer, 2004), mentors' and protégés' individual differences are key factors that warrant investigation (Armstrong, Allinson, & Hayes, 2002;Knox & McGovern, 1988;Noe, 2002;Redmond, 1990b). Studies that have examined relationships between mentoring and individual differences such as cognitive styles, personality, locus of control, learning goal orientation, and mentoring (Armstrong, Allinson, & Hayes, 2002;Ellinger, 2002;Godshalk, & Sosik, 2003;Judge & Kammeyer-Mueller, 2007;Kim & Kim, 2007;Siegel, Smith, & Mosca, 2001) definitely suggest that interpersonal interactions and relationship between the participants are critical to mentoring.…”
Section: Background Of the Studymentioning
confidence: 99%
“…Studies that have examined relationships between mentoring and individual differences such as cognitive styles, personality, locus of control, learning goal orientation, and mentoring (Armstrong, Allinson, & Hayes, 2002;Ellinger, 2002;Godshalk, & Sosik, 2003;Judge & Kammeyer-Mueller, 2007;Kim & Kim, 2007;Siegel, Smith, & Mosca, 2001) definitely suggest that interpersonal interactions and relationship between the participants are critical to mentoring. Particularly, studies that identified correlations between mentor personality and functions of mentoring and outcomes of mentoring (Chang, 1981;Theophilides & Terenzini, 1981;Wilson, Woods, & Gaff, 1974) and protégé personality and functions of mentoring and outcomes of mentoring (Aryee, Lo, & Kang, 1999;Turban & Dougherty, 1994) are important in the context of this study because mentoring is a relationship or interpersonal process where personalities play a part.…”
Section: Background Of the Studymentioning
confidence: 99%